Effects of clinical decision support on the TDM of gentamicin and vancomycin in newborns. Issue 2 (12th March 2012) - Fonzo-Christe, C.; Coehlo, A.; Zaugg, C.; Levy-Jamet, Y.; Pfister, R.; Rimensberger, P.; Guignard, B.; Bonnabry, P.
Abstract : Background: The dosing scheme for gentamicin and therapeutic drug monitoring (TDM) of gentamicin and vancomycin in newborns were evaluated as very heterogeneous in our institution. Once daily dosing (ODD) of gentamicin and trough levels measurement is recommended for most patients to ensure efficacy and reduce blood sampling. Guidelines were developed and implemented as a clinical decision support system. Purpose: To evaluate dosing practices, blood sampling and therapeutic levels. Materials and methods: Retrospective case– control study (01.2010-12.2010 and 04.2008 – 03.2009) in newborns (< 28 days of life) receiving either gentamicin or vancomycin before and after implementation of guidelines. Chart analysis criteria (mean +/-SD (Fisher's exact, Wilcoxon rank sum tests)): % of ODD gentamicin dosing schemes, % of peak levels, mean number of levels sampled, % of therapeutic levels (trough level: gentamicin ≤1 mg/l; vancomycin: 5–10 mg/l). Results: Gentamicin: 132 (cases) versus 102 (controls) totalling 134 patients were included (mean gestational age: 33.8±5.4 versus 34.6±5.2 weeks, p>0.05). After guidelines had been implemented, an ODD scheme was used (97.7 vs 61.6%, p<0.001). Peak level measurement and mean number of levels were significantly reduced (0.9 vs 17.2% resp. 0.8±1.0 vs 1.7±1.4, p<0.001). A significantly higher % of trough levels were ≤1 mg/l (68.5 vs 33.0%, p<0.001). Vancomycin: 38 versus 37 patients included (mean gestational age: 29.1±3.8 vs 30.8±4.1 weeks, p>0.05). After guidelines had been implemented, peak level measurements were significantly reduced (0 vs 25.2%, p<0.001) and a trend to more patients with <2 levels sampled was noted (52.6% vs 29.7%, p=0.061). No differences were observed in the mean number of levels or in the % of therapeutic levels (2.7±3.4 vs 2.6±2.2, resp. 45.7 vs 57.1%, p>0.05). Trough levels > 15 mg/l were significantly more frequent (21.0% vs 5.2%, p=0.004) possibly due to an error in the guidelines. Conclusions: Gentamicin dosing and TDM practices were improved after guidelines had been implemented. The effect of corrected guidelines on vancomycin TDM practice, the financial benefit of reduced blood sampling and clinical benefit should be evaluated in the future.